Potensi Permasalahan Pendaftaran Tanah Sistematik Lengkap (PTSL) - Dian Aries Mujiburohman (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
Abstrak: This paper aims to examine the potential problems of Complete Systematic Land Registration (PTSL) as the government's priority agenda to establish land registration throughout Indonesia. This study uses a normative legal research approach by analyzing the legislation related to land registration, especially PP. 24 of 1997 concerning Land Registration and Ministerial Regulation ATR/Ka. BPN No. 12 of 2017 as amended by Ministerial Regulation No. 6 of 2018. The potential of this problem relates to the issue of tax and income tax payable, human resources, facilities and infrastructure, issues absentee land, maximum excess of land ownership, abandoned land, announcement of physical and juridical data, and problems of application of the principles of contradictoire delimitation. The potential of this problem is described and is given alternative solutions on the implementation of PTSL. Alternative solution is by strengthening the regulation of PTSL in the form of Government Parliament (PP), either by revising PP. 24 of 1997 and by forming a separate PP on PTSL by clarifying the outlined problems.Intisari: Tulisan ini bertujuan untuk mengkaji potensi permasalahan pendaftaran sistematik lengkap (PTSL) sebagai agenda prioritas pemerintah untuk menyelengarakan pendaftaran tanah seluruh Indonesia. Kajian ini mengunakan pendekatan penelitian hukum normatif dengan cara menganalisis peraturan perundangundangan yang berkaitan dengan pendaftaran tanah, khususnya PP No. 24 Tahun 1997 tentang Pendaftaran Tanah dan Peraturan Menteri ATR/Ka. BPN No. 12 Tahun 2017 sebagaimana diubah dengan Permen No. 6 Tahun 2018. Potensi permasalahan ini berkaitan dengan masalah biaya Pajak PPh dan BPHTB terhutang, sumberdaya manusia, sarana dan prasarana, permasalahan tanah absentee, kelebihan maksimum dan tanah terlantar, masalah pengumuman data fisik dan data yuridis, serta masalah penerapan asas kontradiktur delimitasi. Potensi masalah ini di diskripsikan dan diberikan aternatif solusi dalam pelaksanaan percepatan PTSL. Aternatif solusinya adalah dengan cara memperkuat regulasi PTSL dalam bentuk Paraturan Pemerintah (PP) baik dengan cara merevisi PP No. 24 Tahun 1997 maupun dengan membentuk PP tersendiri mengenai PTSL yang pada pokoknya pengaturan isi-nya salah satunya memperjelas permasalahan-permasalahan yang diuraikan diatas.